Genetics and Genomics Nursing in Saudi Arabia: Opportunities and Challenge - Bashatah, Adel S. (Asian Journal of Pharmaceutics (AJP), 2024)
Nurses are critical members of the health-care team, and with sufficient knowledge and training in genetics and genomics, they can contribute significantly to fulfilling the potential of precision medicine in practice and research. The efforts of Saudi Arabia toward genetics and genomics are remarkable. Yet, the voice of nurses in such an important field has not been sufficiently explored. Several potential challenges in the health-care system related to genetics and genomics nursing must be considered. In this article, we outline the challenges and opportunities of nursing genetics and genomics fields in Saudi Arabia.